Indonesian terrorism financing : resorting to robberies - Arianti, Vidia (2014)
A record number of robberies have been perpetrated by terrorists in Indonesia over the past three years. This could be a sign of their inability to secure donations and international funding, the result of counter operations against terrorist and extremist groups.